1992
DOI: 10.2527/1992.7051417x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of swine when fed diets containing canola oil and added copper to alter the unsaturated:saturated ratio of pork fat

Abstract: A 3 x 2 trial was conducted to determine the effects of adding canola oil (0, 5, or 10%) and copper sulfate (0 or 250 ppm Cu) to diets of growing-finishing swine on performance, carcass characteristics, and carcass fat fatty acid composition. The trial used 180 pigs (27 kg). Grower diets (.80% lysine for 0% canola oil diet) were given from 27 to 57 kg of BW and finisher diets (.64% lysine) from 57 to 102 kg. Diets were formulated to constant ME:lysine ratio within the grower and finisher phases. Over the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
30
4
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 12 publications
12
30
4
9
Order By: Relevance
“…No other reports measuring BF in live animals have been found, but other researchers have evaluated the effect of dietary fat on BF depth of carcasses. Similar to the present study, St. John et al (1987) and Myer et al (1992) noted no effect on carcass BF thickness upon feeding high MUFA diets. Others have reported that formulating finishing diets with different fat sources, such as beef tallow (Eggert et al, 2007), soy bean oil (Morel et al, 2006), or poultry fat (Engel et al, 2001) had no effect on average or individual carcass fatness.…”
Section: Backfatsupporting
confidence: 79%
See 3 more Smart Citations
“…No other reports measuring BF in live animals have been found, but other researchers have evaluated the effect of dietary fat on BF depth of carcasses. Similar to the present study, St. John et al (1987) and Myer et al (1992) noted no effect on carcass BF thickness upon feeding high MUFA diets. Others have reported that formulating finishing diets with different fat sources, such as beef tallow (Eggert et al, 2007), soy bean oil (Morel et al, 2006), or poultry fat (Engel et al, 2001) had no effect on average or individual carcass fatness.…”
Section: Backfatsupporting
confidence: 79%
“…However, Castell (1977) reported a decrease in daily gain in pigs fed diets with rapeseed high in MUFA and related this to a lower feed intake, probably due to the rapeseed inclusion itself or the size of the grain in the diet. Supplementing swine diets with 5 and 10% can- ola high in MUFA has been shown to increase weight gain from 57 to 102 kg live weight compared to nonsupplemented animals (Myer et al, 1992). This could be due to differences in the energy concentration of the supplemented diets compared to the control diet used in that trial.…”
Section: Body Weightmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of vegetable oils high in monounsaturated fatty acids (MUFA) as an alternative to those rich in PUFA (Miller et al, 1990;Myer et al, 1992) has reached an increased interest. This was due to the favourable publicity that monounsaturated fats have received in regard to human health (Grundy, 1986), because of its possibility of decreasing saturated and n-6 fatty acids and its low oxidation rate (Rey et al, 2004).…”
Section: Introductionmentioning
confidence: 99%